Thiolated Au18cluster: preferred Ag sites for doping, structures, and optical and chiroptical properties - Molina, Bertha; Tlahuice Flores, Alfredo (Royal Society of Chemistry, 2016)
Recently, the X-ray determined structure of the thiolated Au18 cluster has been reported. In this communication, we addressed a study of structures and chiroptical properties of thiolated Au18 cluster doped with up to ten Ag atoms, which have been calculated by Time Dependent Density Functional Theory (TD-DFT). The number of Ag atoms was steadily varied and more stable isomers showed optical and Circular Dichroism (CD) spectra distinct from that found for the parent Au18 cluster. Doping with more than four Ag atoms results in enhancement of the oscillator strength of the HOMO–LUMO peak and it is expected that this feature can be exploited for photoluminescence applications.